The Effect of Silicon Substitution in Indacenodithiophene‐Based A2‐A1‐D‐A1‐A2‐Type Nonfullerene Acceptors on the Performance of High‐Voltage Organic Solar Cells. Issue 11 (27th September 2022) - Dai, Tingting; Du, Mengzhen; Wang, Helin; Li, Xianda; He, Zehua; Meng, Yuhan; Yang, Fu; Tang, Ailing; Geng, Yanfang; Zhou, Erjun
Abstract : In recent years, the organic solar cells (OSCs) research hotspot is the modification of end groups and alkyl side chains of A‐DA'D‐A‐type nonfullerene acceptors (NFAs). However, the development of novel NFAs by changing the different bridged atom substitution of the central core is lagging behind. Herein, two wide‐bandgap A2 ‐A1 ‐D‐A1 ‐A2 ‐type NFAs with different central cores, namely BTA501 and BTA502, are developed to improve the photovoltaic performance of high‐voltage OSCs. BTA501 adopted an indacenodithiophene (IDT) core, whereas BTA502 applied a silaindacenodithiophene (SiIDT) core. Expectedly, the SiIDT‐based BTA502 exhibits a higher lowest unoccupied molecular orbital level and wider bandgap than BTA501, which thus enhances the open‐circuit voltage ( V OC ) but slightly decreases the short‐circuit current density ( J SC ) of OSCs. Moreover, the stronger self‐aggregation characteristics and weaker π–π stacking of BTA502 severely affect the exciton dissociation and charge transport. When blended with two classic p ‐type polymers J52‐F and PTB7‐Th, both combinations based on BTA502 exhibit inferior device performance compared with BTA501. Excitingly, the device of J52‐F: BTA501 achieves a V OC of 1.037 V with a power conversion efficiency of 11.82% and a J SC of 15.89 mA cm −2, which are among the highest values for high‐voltage OSCs with V OC above 1.0 V. Abstract : Herein, two wide‐bandgap A2 ‐A1 ‐D‐A1 ‐A2 ‐type nonfullerene acceptors with different central cores, namely BTA501 and BTA502, are developed to improve the photovoltaic performance of high‐voltage organic solar cells. Consequently, the device of J52‐F: BTA501 achieves an open circuit voltage ( V OC ) of 1.037 V with a PCE of 11.82%, which are among the highest values for high‐voltage devices with V OC above 1.0 V.